Wave–Particle Interaction in the Upstream of Interplanetary Coronal Mass Ejection Shocks - Shanwlee Sow Mondal; Aveek Sarkar; Sofiane Bourouaine (The Astrophysical Journal)
Shocks associated with interplanetary coronal mass ejections are known to energize charged particles and give rise to solar energetic particles. Many of these energetic particles move ahead of the shock to create a foreshock region. The foreshock region primarily consists of solar wind plasma, exhibiting turbulent velocity and magnetic fields. Such turbulent behavior results from inherent solar wind turbulence modified by energetic particles. We analyze magnetic field data from six such ICME shocks observed by the Wind spacecraft. The analysis of the shock upstream shows that the magnetic power spectral density (PSD) maintains a power-law slope of −5/3. We also identify clear intermittent peaks in the PSD. After characterizing these peaks, we investigate various possibilities for their generation. Our analysis indicates that these peaks in the PSD are due to the resonant interaction of Alfvén waves with the bulk solar wind protons and protons with energy up to 10 keV. However, evidence of Alfvén wave interaction with highly energetic protons is not evident in our analysis, and we anticipate that such evidence is obscured by the prevailing solar wind turbulence in the shock upstream.